Scenic Imagery in the Poems of Youssef Al-Khal and Arthur Christopher BensonA Comparative Study (Journal of the College of Basic Education, 2025)
Scenic imagery in the poems of Youssef Al-Khal and Arthur Christopher Benson is the most prominent feature of visual formation in producing the poetic meaning of the poem, in addition to poetic rhythm and poetic language. The employment of the features of scenic imagery in breaking the restrictions of the traditional poetic structure and bringing it out to new connotations and meanings. This research came to address the problem of the psychological factor in the poet in terms of the multiplicity of his ideas and coming up with a specific idea and conveying it to the recipient in a scenic manner. The objectives of this research are to describe the concept of scenic imagery in the poems of Youssef Al-Khal and Arthur Christopher Benson, and to analyze the forms of scenic imagery in the poems of Youssef Al-Khal and Arthur Christopher Benson, then to show the similarities and differences of scenic imagery in their poems. Based on the "descriptive analytical method" and the "comparative method"; To analyze and compare selected examples from the two collections "The Complete Works" by Youssef Al-Khal and "There Are Many Things" by Arthur Christopher Benson. This research reached the most prominent results, the poetic imagery in Youssef Al-Khal's poems benefited from the scenic aspect as a method that supports the psychological and thematic factor. In Benson's poems, the scenic imagery acquired a contemporary semantic dimension. As for the similarities and differences, the similarity lies in the poetic text's dispensing of different ideas through scenes embodied in the revelation of new connotations, and the difference lies in the visual dimensions that attempt to support the linguistic images.